Political structure and the administration of political system in Iraq (post-ISIS) - Majeed Hameed, Muntasser (Cuestiones Políticas, 2020)
The objective of the investigation was to analyze the structure and administration of the political system in Iraq (post-ISIS). After 2003, the Iraqi political system suffered the fundamental problem of its failure to achieve the political and social inclusion that characterizes democratic systems, to guarantee the establishment of a "state for all", while respecting differences. Political representation has moved from the system of sectarian ethnic components, under the title of consensual democracy, to the representation of leaders and the realization of their interests and the interests of their parties at the expense of the groups that claim to represent them, which complicates the problem. In this sense, the new political system could not represent social pluralism, on the one hand, and could not satisfy the demands of the same components on the other. Methodologically, it is a political investigation in the framework of the analysis of the political system. It was concluded that the search for new balances is a pending issue. While these emerging balances and arrangements are still fragile and immature to the extent required, they represent a clear entry point to reshape the regime's political structure in one form or another.